Georgia Architectural and Historic Properties Survey of 113 and 115 Pear St., Valdosta, Ga., December 1980 - Smith, Bartholomew; Bartholomew, Beth (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 115 Pear St., Valdosta, Ga., December 1980. 2 houses 1 story shiplap sided saddlebag with gabled tin roof. Shed porch held up by square posts. Double hung sash windows with 6/6 and 2/2 lights. Imbricated wood shingles in gables. Set on brick piers. Fair condition. Date of Construction: Prior to 1922. Singles in gables is an unusual feature. Significant as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 115 Pear St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 80.4 MB (84,331,039 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)